Dampak Pan Arabisme Terhadap Identitas Masyarakat Mesir Koptik - Dian Agustina; Iin Suryaningsih (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
This study aims to determine the impact of the Pan Arabism Movement initiated by Gamal Abdul Nasser in 1956-1970 on the religious identity, language, and culture of the Egyptian Coptic society. The method used in this study is a library research method by collecting data from various sources, then analyzing and describing the results of data analysis based on the cultural theory of the Egyptian Coptic society according to Malaty, 1993 and the Pan Arabism Policy theory according to Elie and Onn Winckler Podeh, 2004. Pan Arabism had an identity-changing impact on Egyptian Coptic society. In religion, the freedom to guard and protect their places of worship was restricted and the existence of the Coptic religion began to diminish. In language, the use of Coptic is increasingly restricted and Coptic is almost extinct because it is only used during worship as a liturgical language. Meanwhile, in cultural field, there was an ideological shift in Egyptian society and Egypt became more identical with Arab culture.Keyword - Pan Arabism, Gamal Abdul Nasser, Identity of the Egyptian Coptic Society.